Comparative analysis of Buddhian and Daoi temple architecture of ancient China - Changzhi, Wu (Theory and practice of design, 2022)
The article is devoted to the peculiarities of the architecture of Buddhist and Taoist temple complexes of ancient China. The work is aimed at identifying the religious and geographical features of the distribution and location of temple complexes, comparing the principles and methods of organizing the temple space. Questions are raised of constructive comparison of regional features of sculptural and monumental-decorative decoration of Buddhist and Taoist architectural structures in terms of their similarities and differences. The purpose of this article is to establish and compare the criteria for the distribution and location of complexes, the principles of organizing architectural and landscape compositions, types of structures, features of the sculptural and decorative decoration of Buddhist and Taoist temple complexes. To solve the theoretical issues of building medieval Chinese temples, the following methods were used: the empirical method, the method of comparative analysis, the scientometric method (analysis of the historical experience of designing and building the object under study according to literary sources). The main differences of opposing cultures (philosophy, symbols, concepts of life and death), due to which the architectural space of Buddhist and Taoist temple complexes was formed, were revealed, these include: planning, territorial location, the use of works of fine art (sculptures and paintings), a feature of the and outer temple structure. This article proposed a structural table of the direct influence of two cultures of ancient China on certain criteria for architectural planning, which are identified with the philosophy and geographical location of the temples. The modern vision of the problem of perception of ancient Chinese temple architecture, which has a globalization impact on the temple architecture of Europe, is assessed, which in turn requires the formation of a new comparative analysis on the subject of kinship and differences from the Gothic planning structure. During the study, a number of differences in philosophical and cultural concepts were noted, which leads to polar differences in the nature of the design of temple complexes. All identified criteria were systematized.